Enhancing Power System Stability and Efficiency Using Flexible AC Transmission Systems (FACTS): A Comprehensive Analysis of Control Strategies and Applications - Shinde Sandip; Gandhi N Rajiv; Margarat G. Simi; Khairnar Yogesh; Al-Jawahry Hassan M.; Landage Milind; Naidu K. Kumaraswamy (E3S Web of Conferences)
Flexible AC Transmission Systems (FACTS) play a vital role in enhancing the stability, efficiency, and reliability of modern power systems. With the increasing complexity of power grids due to the integration of renewable energy sources, effective control of power flow, voltage regulation, and stability improvement are critical challenges. FACTS devices, such as Static Synchronous Compensator (STATCOM), Unified Power Flow Controller (UPFC), and Thyristor- Controlled Series Capacitor (TCSC), offer advanced solutions to mitigate these challenges by providing dynamic voltage control, reactive power compensation, and congestion management. This paper presents a comprehensive analysis of various FACTS devices, focusing on their control strategies, applications, and impact on improving power system performance. Simulation results demonstrate the effectiveness of FACTS devices in maintaining voltage stability, optimizing power flow, and minimizing transmission losses, ultimately contributing to a more efficient and resilient power grid.